Nerve Repair with Nerve Conduits: Problems, Solutions, and Future Directions - Rebowe, Ryan; Rogers, Ashley; Yang, Xuebin; Kundu, S. C.; Smith, Thomas L.; Li, Zhongyu (Journal of Hand and Microsurgery, 2018)
Nerve conduits are becoming increasingly popular for the repair of peripheral nerve injuries. Their ease of application and lack of donor site morbidity make them an attractive option for nerve repair in many situations. Today, there are many different conduits to choose in different sizes and materials, giving the reconstructive surgeon many options for any given clinical problem. However, to properly utilize these unique reconstructive tools, the peripheral nerve surgeon must be familiar not only with their standard indications but also with their functional limitations. In this review, the authors identify the common applications of nerve conduits, expected results, and shortcomings of current techniques. Furthermore, future directions for nerve conduit use are identified.
Keywords: nerve injury; nerve conduit; nerve palsy; nerve gap